P646 Histological remission in patients with moderate-to-severe ulcerative colitis undergoing biological therapy: a single-centre experience. (25th January 2019) - Di Ruscio, M; Variola, A; Geccherle, A; Lunardi, G; Castelli, P; Zamboni, G; Riddell, R
Abstract: Background: Histological remission (HR) is emerging as a new treatment target in patients with ulcerative colitis (UC). Biological drugs, as anti-tumour necrosis factor (TNF) agents and anti-integrins, represent the best choice for treating patients with moderate to severe disease. However, 'real-life' data about their efficacy in achieving this goal are limited. The aim of the study was to evaluate the efficacy of biological drugs to achieve histological remission in UC patients. Methods: We enrolled in a retrospective observational study adult patients with moderate-to-severe UC referring between 2014 and 2018 to IBD Unit (Negrar Hospital), both naïve and experienced to a previous Anti-TNF. We performed endoscopic (by Mayo Endoscopic Subscore, MES) and histological (Nancy Histological Index, NHI, a recent validated score) at baseline (before starting biological therapy) and at Week 48 (control time). Histological remission was defined as NHI < 2. The worst colonic segment was used for the assessment of disease activity. Fisher exact test was used for the statistical analysis (a p -value of <0.05 was considered statistically significant). Results: Sixty-one patients were included. At baseline median MES was 2.6 (2–3), median NHI was 3.5 (2–4). Twenty-eight patients were treated with Infliximab (IFX), 10 with Adalimumab (ADA), 20 with Golimumab (GOL), 3 with Vedolizumab (VDZ), all according to conventional regimen. At Week 48, 26.2% (16/61) of patients achieved histological remission; the subgroup analysis showed that 21.4% (6/28) of patients treated with IFX, 60% (6/10) of patients treated with ADA and 20% (4/20) of patients treated with GOL achieved histological remission. All 3 patients treated with VDZ still showed histologically active disease at control time (NHI ≥ 2). There were no significant differences among drugs ( p = 0.082). 42.6% (26/61) of patients achieved endoscopic remission (MES 0 or 1). All patients achieving histological remission were also in endoscopic remission; of these, 62.5% (10/16) had a MES=0. Median MES and NHI significantly improved at Week 48 (1.8 and 2.7, respectively; p < 0.001). There were no differences between naïve and experienced patients ( p = 0.703). Conclusions: All anti-TNF agents are able to achieve histological remission in patients with moderate-to-severe UC. For considerations about VDZ more data are required.